Ni2P–CoP hybrid nanosheet arrays supported on carbon cloth as an efficient flexible cathode for hydrogen evolution. Issue 43 (18th October 2016) - Wang, An-Liang; Lin, Jing; Xu, Han; Tong, Ye-Xiang; Li, Gao-Ren
Abstract : Here we report a new type of Ni2 P–CoP hybrid nanosheet arrays (HNSAs) supported on carbon cloth (CC) (Ni2 P–CoP HNSAs/CC) as an efficient flexible cathode for the hydrogen evolution reaction (HER). Abstract : Here we report a new type of Ni2 P–CoP hybrid nanosheet array (HNSAs) supported on carbon cloth (CC) (Ni2 P–CoP HNSAs/CC) as an efficient flexible cathode for the hydrogen evolution reaction (HER). This synthesized Ni2 P–CoP HNSAs/CC shows excellent electrocatalytic performance for the HER in both acid and alkaline solutions compared with Ni2 P/CC and CoP/CC cathodes that have been considered to be good candidates for the HER. The significantly improved electrocatalytic performance of Ni2 P–CoP HNSAs/CC can be attributed to the special surface effects of hybrid nanosheet arrays and synergistic effects between Ni2 P and CoP. The Ni2 P–CoP HNSAs/CC shows excellent flexibility and exhibits unchangeable electrochemical performance under the various distorted states, such as bending and twisting sates.